A molecular marker for, and the organization of, a cluster of loose smut resistance genes in oat - Kibite, Solomon; Rossnagel, Brian; Eckstein, Peter; Hay, Donna; Menzies, Jim; Dill-Macky, Ruth; Scoles, Graham (MTT, 2004)
Loose smut (Ustilago avenae) resistance breeding is hampered by the many distinct smut races, and the different, poorly characterized resistance genes. Three pathotypes (A13, A60, A617) represent the most common races present in the prairie regions of western Canada (Kibite et al. 2000). Markers linked to a group of smut resistance genes located on linkage group 14 (Kanota/ Ogle) have been developed (Eckstein et al. 2002). One co-dominant SCAR marker was used to study the relationship between the marker and the three resistance genes. Molecular markers and plant populations used were described in Eckstein et al. (2002). Another population (OT369/89Ab4088) segregating for the three genes was also evaluated. All lines were inoculated with separate isolates of A13, A60, and A617 using a vacuum protocol, and grown over several locations and years in western Canada. SCAR marker Ua300co (co-dominant) was linked (~ 5 cM) to a resistance gene specific for pathotype A13. Two other pathotype specific genes clustered on the same side of the marker at genetic distances of 8 cM (A617) and 18 cM (A60). The genes are linked in coupling and are likely often inherited as a group. Attempts to find a flanking marker for the cluster are in progress. Eckstein et al. 2002. In: American Oat Workers Conference, Wilmington, NC, USA, May 5-7, 2002. pp33; Kibite et al. 2000. In: Cross, R.J. (ed). Proceedings of the 6th International Oat Conference, Lincoln, NZ. November 13-16 2000. pp298-301.
Keywords: Ka; oat; loose smut; disease resistance; marker; gene cluster